The Influence of Good Corporate Governance towards Company’s Value: Case Study of Indonesian Banking Listed on the Indonesia Stock Exchange - Bayu Aji Sumantri, Muhammad; Andriani Hapsari, Ajeng (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the effect of Good Corporate Governance (GCG) toward the company’s value. The object of the study is Indonesian banking listed on the Indonesia Stock Exchange (IDX). Tobin’s Q is used as the dependent variable. Meanwhile, size of board directors, size of board of commissioner, independent shareholders, large shareholders and institutionalized shareholders are the independent variables. These variables are analyzed by the data panel regression method. The finding of this study is that size of board of directors and size of board of commissioner have a significant impact. Meanwhile, independent shareholders, large shareholders and institutionalized shareholders do not have a significant impact toward the company’s value. This finding is believed to contribute to the development of the GCG in Indonesia.